2019
DOI: 10.1007/s00148-019-00733-w
|View full text |Cite
|
Sign up to set email alerts
|

Female genital mutilation and migration in Mali: do return migrants transfer social norms?

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…FGM/C is a strong social norm that makes it difficult for individuals to challenge, as the practice often occurs in societies where norms of collectivity are predominant. The impact of these different settings on social norm change and human rights is not in the scope of this paper and has been discussed elsewhere by various authors (see for example Diabate et al [45], UNICEF [46], Leye et al [47]).…”
Section: Discussionmentioning
confidence: 99%
“…FGM/C is a strong social norm that makes it difficult for individuals to challenge, as the practice often occurs in societies where norms of collectivity are predominant. The impact of these different settings on social norm change and human rights is not in the scope of this paper and has been discussed elsewhere by various authors (see for example Diabate et al [45], UNICEF [46], Leye et al [47]).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge is to identify those opinion leaders and target them, which can be seen as trying to dene the network structure that matters for a specic innovation. 19 Thus, in a study concerned with FGC, Diabate and Mesple-Somps (2014) found that Malian migrants to non-FGC countries play an important role in inuencing decisions about FGC when they come back to their village (after controlling for selection into migration and return migration).…”
Section: The Role Of Opinion Leadersmentioning
confidence: 99%
“…Ferrant and Tuccio (2015) argue that South-South migration leads to a convergence of female discrimination in origin countries towards levels of destination countries. Diabate and Mesplé-Somps (2019) provide evidence that Malian return migrants from countries, where female circumcision is not common, have a signicant negative eect on the spread of female genital mutilation. Lodigiani and Salomone (2020) show that emigration induces female political empowerment, but conditional on the female parliamentary participation in destination countries.…”
Section: Introductionmentioning
confidence: 90%